MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MULTIKULTURAL DI SEKOLAH MENENGAH ATAS - Zamathoriq, Defan; Subur, Subur (Jurnal Ilmiah Mandala Education (JIME), 2022)
The learning model of Islamic Religious Education in senior high schools has recently been highlighted by many education observers. This situation is natural considering that from year to year racism continues to occur in the world of education. The nation of Indonesia's caliber with great heterogeneity is indeed very possible for friction between students, paying attention to all these possibilities, this paper tries to analyze the multicultural-based learning model of Islamic Religious Education in senior high schools. This study uses the library research method by analyzing the results of the study of books and scientific journals. This research produces a multicultural-based PAI learning model in which students can absorb and practice multicultural-based PAI learning in high school so that it has implications for respect, acceptance and appreciation for differences between students.